2015
DOI: 10.5152/akd.2014.5732
|View full text |Cite
|
Sign up to set email alerts
|

Nonthyroidal illness syndrome in off-pump coronary artery bypass surgery

Abstract: Objective:It is well known that coronary artery bypass grafting (CABG) is often the cause of non-thyroidal illness syndrome (NTIS). Nonthyroidal illness syndrome (NTIS) is a state characterized by low levels of tri-iodo-thyronine (T3) and high levels of reverse T3 (rT3), with normal or low levels of thyroxin (T4) and normal, low-normal, or low levels of thyroid-stimulating hormone (TSH). Today, there are two main techniques of CABG: CABG with the use of cardiopulmonary bypass (on-pump coronary artery bypass - … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“…In this regard, the impact of CABG-associated ESS on cardiac function is complicated, including upregulating gene expression of cardiac contractile proteins as well as leading to peripheral vasodilation and so as to ultimately decreasing systemic vascular resistance. 2,4,9 Crucial changes in cardiac functions and structure have been found in various original articles involving ESS 3,9 and further confirmed in a meta-analysis regarding 41 studies. 16 It is thus plausible that the decreased T3 in patients with CABG-associated ESS would exacerbate the pathologic cardiac function and thus contribute to increased risk of adverse postoperative outcomes.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…In this regard, the impact of CABG-associated ESS on cardiac function is complicated, including upregulating gene expression of cardiac contractile proteins as well as leading to peripheral vasodilation and so as to ultimately decreasing systemic vascular resistance. 2,4,9 Crucial changes in cardiac functions and structure have been found in various original articles involving ESS 3,9 and further confirmed in a meta-analysis regarding 41 studies. 16 It is thus plausible that the decreased T3 in patients with CABG-associated ESS would exacerbate the pathologic cardiac function and thus contribute to increased risk of adverse postoperative outcomes.…”
Section: Discussionmentioning
confidence: 76%
“…3 CABG is a considerable stress for coronary heart disease (CHD) patients, especially for patients with high-risk cardiac surgery, and can lead to the occurrence of ESS in a huge number of patients undergoing this kind of surgery. 2,4,5 Recent studies further confirmed CABG-associated ESS occurred in two-thirds of CHD patients and off-pump CABG did not improve the postoperative thyroid function. 4,5…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…NTIS is a state that is characterized by low triiodothyronine (T3) levels and high reverse T3 levels, with normal or low thyroxine levels and normal, low-normal, or low thyroid-stimulating hormone (TSH) levels. NTIS occurs in a significant number of patients undergoing CABG ( 2 ). The low T3 level is associated with higher marker levels of inflammation and increased endothelial dysfunction.…”
mentioning
confidence: 99%
“…We want to congratulate Caluk et al ( 1 ) for their fluent and impressive article “Nonthyroidal illness syndrome in off-pump coronary artery bypass surgery” published in Anatolian Journal of Cardiology 2015: 15: 836-42. As they mentioned, many reasons such as surgical operations, acute and chronic systemic diseases, sepsis, and severe burns may result in nonthyroidal illness syndrome (NTIS).…”
mentioning
confidence: 99%